Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (Collaborative Unity and Existential Responsibility, 2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

QCGN Intervienes in B.C. School Board Case at Supreme Court of Canada - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Memorandum of Understanding Between Acadians in New Brunswick, English-speaking Quebecers and Franco-Ontarians - Société de l’Acadie du Nouveau-Brunswick (SANB); Quebec Community Groups Network (QCGN); Assemblée de la francophonie de l’Ontario (AFO) (2019)
Keywords: Official Language Minority Community (OLMC)

Modernizing the Official Languages Act : The Commissioner of Official Languages' Recommendations for an Act that is Relevant, Dynamic and Strong - Canada. Office of the Commissioner of Official Languages (2019)
It has been 50 years since the first Official Languages Act was passed. While we celebrate the progress and many successes achieved since 1969, it is a good time to conduct and in-depth review of official languages needs and think about whether the tools offered by the Act meet those needs effectively. The Commissioner’s repeated calls to modernize the Act have been echoed across Canada by both language groups, highlighting the urgent need to review the current legislative framework and draft new regulations to meet the expectations and reflect the realities of all Canadians. The Commissioner is therefore recommending a holistic approach to modernizing the Act that goes well beyond legislative and regulatory change. To create a cultural shift so that linguistic duality can reach its full potential across Canada, he has made 18 recommendations under the three pillars of his vision for an Act that is relevant, dynamic, and strong.

Minnie H. Bowen's Canada : Documentary Record for Elementary School - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Documentary Record for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Student's Workbook for Elementary - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Student's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for elementary school - Eastern Townships Resource Centre (ETRC) (2019)

Minnie H. Bowen's Canada : Teacher's Workbook for Highschool - Eastern Townships Resource Centre (ETRC) (2019)

Message For Our Veterans - Maurice, Cornella (2019)

Neighbours of Rouyn-Noranda Guide to Federal Election Candidates for Abitibi-Téscamingue - Neighbours Regional Association of Rouyn-Noranda (2019)
Here is a brief guide to your candidates for the Abitibi-Témiscamingue riding, and some of the party platforms on key issues. Neighbours remains non-partisans and is only attempting to provide information not an endorsement.

Y4Y Quebec Opposes the Cancellation of the French-language University in Ontario and Expresses its Solidarity with the Young Franco-Ontarians Who Worked on the Project - Youth for Youth Québec (Y4Y Québec) (2018)

QCGN Denounces Cuts to French Language Services in Ontario - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

[Letter to René Cormier, Chair of the Senate Standing Committee on Official Languages, from Geoffrey Chambers, QCGN President, re: the Official Languages Act] - Chambers, Geoffrey (2018)

An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

Brief by the Consortium of Official Language Minority Community Media, Presented to the Standing Senate Committee on Official Languages Within the Context of its Study on Canadians' Views About Modernizing the Official Languages Act - Sonier, Francis; Demers, Paul; Bonspiel, Steve (2018)
The Consortium of Official Language Minority Community Media (the Consortium) is an alliance of the three national organizations representing official language minority community media in Canada: the Association de la presse francophone (APF), the Alliance des radios communautaires du Canada (ARC du Canada) and the Quebec Community Newspapers Association (QCNA). Since 2016, the Consortium has been the common voice of all three of its members on a number of issues.
Keywords: Official Language Minority Community (OLMC)

QCGN Applauds Priorities in Commissioner's Annual Report - Quebec Community Groups Network (QCGN) (2018)

Message For Our Veterans - Maurice, Cornella (2018)

QCGN Project to Involve Youth in Canada's Sesquicentennial - Quebec Community Groups Network (QCGN) (2017)

QCGN Invites Meilleur to Become Acquainted with English-speaking Quebec - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Hopeful About Opportunities for Official Language Minority Communities in Federal Budget - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

Bilingual Young Quebecers Leading the Way to Canada's Future - Quebec Community Groups Network (QCGN) (2017)

QCGN Welcomes Resurrection of Independent Court Challenges Program - Quebec Community Groups Network (QCGN) (2017)

Active Offer : A Culture of Respect, a Culture of Excellence - Canada. Office of the Commissioner of Official Languages (2017)

English-speaking Quebec Must Have a Stronger Voice in Conversation About Official Languages - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Public Consultation on Canadian Content in a Digital World - English Language Arts Network (ELAN); Forget, Bettina; Rodgers, Guy (2016)
Keywords: Official Language Minority Community (OLMC)

QCGN Advocates for More Flexible Regulations for Provision of Federal Minority Language Services - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Brief to the House of Commons Special Committee on Electoral Reform - Quebec Community Groups Network (QCGN) (2016)
The QCGN is concerned that the Government of Canada has not provided Canadians a specific electoral system on which to be consulted. Arriving at a recommended electoral system has been delegated to this Committee, with the decision on which system to pursue resting with the government. Members of the Committee undoubtedly understand the complexity of various systems under consideration, and the esoteric nature of the material. Indeed, so far the discussion at this Committee has been dominated by specialists, a term used broadly to include technical experts, and people and groups with an ongoing interest and specialization in electoral systems. This should come as no surprise when beginning with a blank sheet of paper, and indeed, the Committee is mandated to seek out expert testimony.

Quebec Youth Lead the Way to Sesquicentennial Celebrations - Quebec Community Groups Network (QCGN) (2015)

AELAQ Reading Fund Covers Honoraria and Travel Costs for Public Readings Across Canada - Association of English-language Publishers of Quebec (AELAQ) (2015)

Public Readings by Authors Published by Members of the Association of English-language Publishers of Quebec (AELAQ) - Association of English-language Publishers of Quebec (AELAQ) (2015)
Keywords: Official Language Minority Community (OLMC)

Message For Our Veterans - Maurice, Cornella (2015)

Federal Institutions Must Properly Support Quebec's English-speaking Seniors, says Graham Fraser - Office of the Comissioner of Official Languages (2013)

QCGN Congratulates Shelly Glover New Minister for Canadian Heritage and Official Languages - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Feasibility Study for a Rapid Maritime Link for Passengers of the Lower-North-Shore - Conseils & Stratégies pour l'Avenir des Régions (PAR) (2013)
This study relates to the feasibility of a maritime link for passengers on the Lower North Shore aiming at meeting a need shown for accessibility of both citizens and tourist alike with an affordable, rapid link with improved frequency, between the different communities and lasting the summer period, departures from Natashquan and Blanc-Sablon.

QCGN Approves New Roadmap for Canada's Official Languages - Quebec Community Groups Network (QCGN) (2013)

Federal Budget Indicates Government Comitted to Quebec's English-speaking Minority with a Renewed Roadmap for Official Languages - Quebec Community Groups Network (QCGN) (2013)

[Study on the use of the Internet, new media and social media and respect for Canadians' language rights : A study on Air Canada's obligations under the Official Languages Act : Remarks to the Standing Committee on Official Languages] - Quebec Community Groups Network (QCGN) (2011)

Linda Leith Remarks to OCOL Part VII Forum - Leith, Linda (2011)
Keywords: Official Language Minority Community (OLMC)

Roadmap to Canada's Linguistic Duality 2008-2013 - Donnelly, Robert (2010)
Remarks to the Standing Committee on Official Language
Keywords: Official Language Minority Community (OLMC)

The Official Languages Act and the English-speaking Community of Quebec : Learning from the Past - Donnelly, Robert (2010)
Keywords: Official Language Minority Community (OLMC)

The Official Languages Act and the English-speaking Community of Quebec : Looking to the Future - Johnston, Nicola (2010)
Remarks to the Standing Committee on Official Languages

What is Bill C-32? - English Language Arts Network (ELAN) (2010)
Bill C-32 is officially known as the Copyright Modernization Act. It was an attempt at a “Balanced Copyright” act introduced in Parliament on June 2, 2010, by the Conservative Party — Honourable Tony Clement, Minister of Industry, and the Honourable James Moore, Minister of Canadian Heritage and Official Languages. It contains changes to Canadian Copyright Law that are hotly contested by artists and authors of cultural media. The Bloc, NDP and Liberal parties are opposed to the act being passed in its current state, and are calling for amendments to be made.
Keywords: Official Language Minority Community (OLMC)